Perm Academic Project: How It All Started - Igor Konstantinovich Kiryanov (Известия Уральского федерального университета. Серия 2: Гуманитарные науки)
This paper considers the process of institutionalisation of the first academic establishments in Perm, i. e. the Department of Polymer Physics, the Department of Microorganism Breeding and Genetics of the Institute of Plant and Animal Ecology and the Laboratory of Complex Economic Research of the Institute of Economics, which began their activities in 1971 in the system of the Ural Scientific Centre of the USSR Academy of Sciences. The research methodology is based on the concepts of “center — periphery: the diffusion of innovations” and “economy of approvals / bargaining”, the effectiveness of which in studying scientific and technical policy and academic “construction” in the eastern regions of the country is demonstrated in the papers of E. G. Vodichev and Yu. I. Uzbekova. The study draws upon administrative documents of the supreme party and Soviet bodies (decisions of the CPSU congresses, resolutions of the CPSU Central Committee and the USSR Council of Ministers); office documents of the Perm Regional Committee of the CPSU, the Presidium of the USSR Academy of Sciences, the Ural Scientific Centre, divisions of the Perm group of scientific institutions (resolutions, business correspondence, project and reporting documentation); periodicals (Vestnik AN SSSR, Nauka Urala); ego-documents (memories of the first heads of Perm academic institutions, autobiographical and diary entries of M. N. Stepanov). The author examines the grounds for formulating the Perm academic project (the general trend in Soviet scientific and technical policy; the factor of Perm being the “capital city” of the Western Urals; the achievements of Perm scientists and the scientific schools that were being formed). Additionally, the article demonstrates the complex process of coordinating the statuses and names of specific institutions, giving a classification of the types of main actors in accordance with their roles in the project (customer, developer, “sponsor”, “lobbyist”).